Необходимо приравнять к общему знаменателю ((2*x+3)/(x^2+4))+((-2*x-6)/(2*x^2+4))

Необходимо приравнять к общему знаменателю ((2*x+3)/(x^2+4))+((-2*x-6)/(2*x^2+4))
Гость
Ответ(ы) на вопрос:
Гость
[latex] \frac{2x+3}{ x^{2} +4} + \frac{-2x-6}{2 x^{2} +4} = \frac{2x+3}{ x^{2} +4} + \frac{-2(x+3)}{2( x^{2} +2)} = \frac{2x+3}{ x^{2} +4} - \frac{x+3}{ x^{2} +2} = [/latex] [latex] \frac{2x+3}{ x^{2} +4} + \frac{-2x-6}{2 x^{2} +4} = \frac{2x+3}{ x^{2} +4} + \frac{-2(x+3)}{2( x^{2} +2)} = \frac{2x+3}{ x^{2} +4} - \frac{x+3}{ x^{2} +2} = \frac{ 2x+3^{ x^{2} +2} }{ x^{2} +4} - \frac{ x+3^{ x^{2} +4} }{ x^{2} +2} [/latex] [latex]= \frac{(2x+3)( x^{2} +2)}{( x^{2} +4)( x^{2} +2)} - \frac{(x+3)( x^{2} +4)}{ ( x^{2} +2)( x^{2} +4)} = \frac{(2 x^{3} +4x+3 x^{2} +6)-( x^{3} +4x+3 x^{2} +12)}{ ( x^{2} +2)( x^{2} +4)} = [/latex] [latex]= \frac{(2x+3)( x^{2} +2)}{( x^{2} +4)( x^{2} +2)} - \frac{(x+3)( x^{2} +4)}{ ( x^{2} +2)( x^{2} +4)} = \frac{(2 x^{3} +4x+3 x^{2} +6)-( x^{3} +4x+3 x^{2} +12)}{ ( x^{2} +2)( x^{2} +4)} = [latex]= \frac{(2x+3)( x^{2} +2)}{( x^{2} +4)( x^{2} +2)} - \frac{(x+3)( x^{2} +4)}{ ( x^{2} +2)( x^{2} +4)} = \frac{(2 x^{3} +4x+3 x^{2} +6)-( x^{3} +4x+3 x^{2} +12)}{ ( x^{2} +2)( x^{2} +4)} \\ \\ =\frac{ x^{3} -6}{( x^{2} +2)( x^{2} +4)} [/latex][/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы